Comparison of characteristics of thin-film transistor with In2O3 and carbon-doped In2O3 channels by atomic layer deposition and post-metallization annealing in O3. (11th February 2021) - Kobayashi, Riku; Nabatame, Toshihide; Onaya, Takashi; Ohi, Akihiko; Ikeda, Naoki; Nagata, Takahiro; Tsukagoshi, Kazuhito; Ogura, Atsushi
Abstract: Characteristics of thin-film transistors (TFTs) with amorphous In2 O3 (InO1.2 ) and carbon-doped In2 O3 (InO1.16 C0.04 ) channels by post-metallization annealing (PMA) process were investigated. The InO1.2 TFT changed from metallic to switching behavior after PMA at 200 °C. In contrast, the InO1.16 C0.04 TFT exhibited superior properties such as a threshold voltage ( V th ) of 3.2 V and a high mobility of 20.4 cm 2  V −1  s −1 at PMA 150 °C because of the reduction of excess oxygen vacancies. A large negative V th shift was observed for the InO1.2 TFT for 10 800 s in N2 under zero bias voltage while there was no V th change for the InO1.16 C0.04 TFT.